Evaluation of the diffusion capacity of calcium hydroxide pastes through the dentinal tubules - Mori, Graziela Garrido; Ferreira, Fábio Cézar; de Souza Batista, Fábio Roberto; de Siqueira Godoy, Alessandro Mauro; Nunes, Daniele Clapes [UNESP] (FapUNIFESP (SciELO), 2009)
This study aimed to evaluate the diffusion capacity of calcium hydroxide pastes with different vehicles through dentinal tubules. The study was conducted on 60 extracted single-rooted human teeth whose crowns had been removed. The root canals were instrumented and divided into 4 groups according to the vehicle of the calcium hydroxide paste: Group I - distilled water; Group II - propylene glycol; Group III - 0.2% chlorhexidine; Group IV - 2% chlorhexidine. After placement of the root canal dressings, the teeth were sealed and placed in flasks containing deionized water. After 1, 2, 7, 15, 30, 45 and 60 days, the pH of the water was measured to determine the diffusion of calcium hydroxide through the dentinal tubules. The data were recorded and statistically compared by the Tukey test. The results showed that all pastes presented a similar diffusion capacity through dentin. Group IV did not present difference compared to group I. Group II presented difference compared to the other groups, as did Group III. In conclusion, groups I and IV presented a better diffusion capacity through dentin than groups II and III; 2% chlorhexidine can be used as a vehicle in calcium hydroxide pastes. © 2009 Sociedade Brasileira de Pesquisa Odontológica.
Keywords: Calcium hydroxide; Chlorhexidine; Dentin; calcium hydroxide; chlorhexidine; drug vehicle; root canal filling material; chemistry; dentin; diffusion; endodontics; human; metabolism; pH; vehicles; Calcium Hydroxide; Diffusion; Humans; Hydrogen-Ion Concentration; Root Canal Filling Materials; Root Canal Preparation; Vehicles